A qualitative analysis of Arabic language websites about extraction of third molars - Muath Saad Alassaf; Mohannad Mohammed Abu Aof; Osama Ayidh Alharbi; Abdulrahman Turkustani; Moataz Ibrahim Karbouji; Nebras Althagafi; Ahmed Mohammed Almghamsi; Ghayda Yousof Zolaly; Shadia Elsayed (Digital Health)
Aim The study aimed to evaluate the quality and readability of Arabic-language web-based online information regarding surgical third molar extraction. Methods In this observational web-based analytical study, the top 150 Arabic search results for surgical wisdom tooth extraction were collected from Google, Yahoo, and Bing. The quality of the websites was evaluated using the DISCERN tool and the Journal of American Medical Association (JAMA) guidelines for online content analysis. Readability was measured using the Flesch-Reading Ease (FRE) scale, the Flesch-Kincaid Grade Level (FKGL) scale, and the Simplified- Measure of Gobbledygook (SMOG). Results A total of 450 websites related to the extraction of wisdom teeth were initially identified. 146 websites were included in the final analysis after exclusion according to specific exclusion criteria. Significant difference was observed in the domain of treatment alternatives and the quality of information provided, according to the DISCERN criteria. The median scores for reliability-related questions ranged from 1.5 to 4.5. The overall quality rating had a median score of 2.5 (IQR = 0.5). There were significant differences in the number of achieved JAMA items per webpage between the groups (P-value = 0.000). However, there was no significant difference in the DISCERN quality evaluations between the affiliations (P-value = 0.450). Conclusion the study results indicating a broad spectrum in the explicitness and relevance of information with moderate quality across the evaluated websites and the investigation revealed significant variations in the content quality and readability provided by websites belonging to various affiliations, with non-profit websites generally achieving higher scores in JAMA criteria and readability measures.